ANALISIS DETERMINAN FAKTOR RISIKO DIABETES MELITUS TIPE II DI PUSKESMAS BATUNADUA TAHUN 2019 - Ritonga, Nefonavratilova; Siregar, Robiah Annum; Nasution, Nurul Hidayah; Ramadhini, Delfi (Universitas Aufa Royhan, 2019)
Diabetes Mellitus is a chronic metabolic disorder that occurs insulin deficiency or insulin retention. The latest Riskesdas data in 2013 shows the prevalence of DM of 1.5 million for the total population throughout Indonesia. Based on data from the Padangsidimpuan City Health Office who suffer from Diabetes Mellitus in 2018 as many as 2,416 people. Batunadua Health Center is one of the most contributing Puskesmas in DM cases, 257 people. This type of research is a survey research that is analytic observation with case control design. The population of this study was 60 people with diabetes mellitus who were registered at the Batunadua Health Center with a accidental sampling of 30 and a control sample of 30. The sampling technique was carried out in total sampling. The results showed that respondents had a family history of suffering from DM Type II as many as 36 respondents (60%), were obese as many as 32 respondents (53.3%) and respondents smoked as many as 32 respondents (53.3%). From this study it was concluded that family history risk factors (p value=0,004; OR=4,667), obesity (p value=0,001; OR=7,667), smoking habits (p value=0,004; OR=5,500) are associated with Type II Diabetes Mellitus in Batunadua Health Center in 2019. It is hoped that it can maintain blood sugar levels to stay in a normal state, stop smoking, reduce weightfor obese patients, and do sports activities to reduce the risk of developing diabetes mellitus.